Thecarer’s burden of an elderly person according functional capacity of an elderly person - Niedorys, Barbara; Mikos, Monika; Michalczyk, Klaudia; Młynarczyk, Joanna; Rząca, Marcin Stanisław; Bartoszek, Agnieszka (Journal of Education, Health and Sport, 2018)
Introduction: The Polish society is aging, which means that the number of people over 60 is increasing. Due to the consequences of old age, these people often require care, which to a varying degree is the cause of the carer’s burden. Aim: Assessmentthe carer’s burden of an elderly person according functional capacity of an elderly person. Material and methods: A group of 120 carers of the aged from 20 to 87 years old, living in south-eastern Poland in the villages (40%) and in the city (60%) were examined.The Cope questionnaire assessing the carer’s burden and the ADL and I-ADL scale was used to collect the data to assess the functional capacity of the pupils. The author’s questionnaire was also used. Results: Most carers of the elderly are women (82.5%) who are usually members of the senior family.A significant number of caregivers (94%) observed a negative impact of care on the life situation. Conclusions: Providing care to an elderly person is a source of stress for the caregiver. The degree of relationship affects the perception of the positive value of care by caregivers.The higher I-ADL score obtained by the mentor has a negative impact on the carer’s functioning. Carers gain little satisfaction from taking care, but they feel supported in their role.